Nursing care for a patient after an ischemic stroke - Foks, Klaudia; Jakubowska, Klaudia Olga; Chruściel, Paweł; Nalepa, Dorota; Kościołek, Aneta; Bieniak, Monika; Pawłowski, Piotr (Journal of Education, Health and Sport, 2019)
Introduction and aim of the study. More than half of ischemic strokes occur above the age of 65, so a stroke is above all a disease of an old age. The problem of a stroke is crucial, because apart from a high mortality rate it also entails a disability. The aim of the study was to determine the scope of nursing care for the patient after an ischemic stroke.Methods and materials. The study was based on the case study method with the use of the following research techniques: documentation analysis, an interview, measurement and observation. Moreover, the study tools applied comprised: an individualized nursing care plan, Barthel Scale, Glasgow Scale, Dutch Scale, the authors’ own test examining the patient’s knowledge.Criteria for the care categories.Findings. After the interview, the biopsychosocial status of the patient was assessed. Nursing diagnoses were made using the empirical data for this purpose. Conclusions. The sudden occurrence of the disease, hospitalization and lack of support from relatives is a difficult and critical situation for the patient, and it disturbs normal functioning in all spheres: biological, psychological and a social one.